Prevalence of Asthma and Its Association with Daily Habits in Jimma Town, Ethiopia - Eden Yitna Tefereedgn; Andualem Mossie Ayana (Open Journal of Asthma - Peertechz Publications, 2018)
Background: Many studies showed a low risk of asthma in sub-Saharan countries. However, due to indoor pollutions and environmental hazards, developing countries are always the prior victims of all types of respiratory illnesses including asthma. Jimma, south-western Ethiopia, is known by its wide range of vegetations including khat and coffee. Together with high plantation of those cash crops, there is widespread consumption of them by the locals. Objective: To investigate prevalence and severity of bronchial asthma and its association with daily habits in Jimma town, Ethiopia Methods and Materials: A community-based cross-sectional study was conducted in Jimma town on 1300 participants. Systematic random sampling technique was employed to select households. Semistructured questionnaire and pulmonary function tests were used to collect data. SPSS was used to execute simple descriptive, independent t-tests and chi-square.